Tinjauan Hukum Pidana Terhadap Kejahatan Kesusilaan Yang Dilakukan Oleh Anggota Dewan Perwakilan Rakyat Daerah (Studi Kasus Di Pengadilan Negeri Soe) - Selan, Nadia Melisa; Fallo, Debby F. Ng; Wilhelmus, Bhisa Vitus (Law Faculty, Nusa Cendana University, 2025)
This study analyzes the main legal issues in the Soe District Court Decision No. 38/Pid. B/2021 relating to the application of Article 281 paragraph (2) of the Criminal Code (maximum sentence of 2 years and 8 months) for crimes against morality committed by members of the DPRD, while the alternative charge of Article 289 of the Criminal Code (sentence of 9 years) was not applied without adequate legal explanation. This study shows that the defendant has been proven to have committed repeated non-penetrative sexual harassment in front of witnesses, with the victim suffering from Post-Traumatic Stress Disorder (PTSD) based on the results of a psychological examination. The 8-month sentence imposed is considered disproportionate to the impact of the trauma experienced by the victim, the frequency of the act, the perpetrator's position as a public official, and a similar verdict handed down at the Yogyakarta District Court which reached 1.5 years. Fundamental criticisms include the use of the mitigating factor of